CULTURE SHOCK: PENGELOLAAN KECEMASAN DAN KETIDAKPASTIAN DIRI PADA MAHASISWA PERANTAU DI YOGYAKARTA - Seiren Ikhtiara (Jurnal Komunikasi dan Kajian Media, 2025)
Students who migrate from outside Java Island to Yogyakarta often face cultural adaptation challenges that trigger anxiety and self-uncertainty. Differences in values, norms, and communication styles lead to their perception as "strangers" within campus social interactions. This study aims to analyze the personal strategies employed by migrant students at UIN Sunan Kalijaga in managing anxiety and self-uncertainty resulting from culture shock. The research is grounded in the Anxiety/Uncertainty Management (AUM) Theory, which emphasizes the importance of managing anxiety and uncertainty in intercultural communication. This study adopts a qualitative approach with a case study method, involving ten informants from the Islamic Communication and Broadcasting program selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation. The findings reveal that students employ five main strategies to cope with culture shock: conducting self-assessment during interactions, enhancing self-confidence, building interpersonal relationships, understanding the local culture, and managing others’ perceptions positively. These results highlight that successful adaptation is not solely influenced by external conditions but is largely determined by the individual's internal awareness and coping strategies. The study contributes theoretically to the field of intercultural communication and offers practical implications for higher education institutions to support students from diverse cultural backgrounds.